Synchronous Dual Primary Malignancies of Lung and Colon: A Case Report with Review of Literature Emphasizing the Role of Molecular Profiling in Diagnostic Differentiation - Maheshwari, Udip; Morzaria, Disha; Chaudhari, Krushna; Bose, Chirantan; Maniar, Vashishth (Indian Journal of Medical and Paediatric Oncology, 2025)
Multiple primary malignant tumors (MPMT), particularly when presenting synchronously—defined as two or more distinct primary malignancies diagnosed within 6 months—are rare and present considerable diagnostic and therapeutic challenges. We report a case of a 75-year-old male patient with no considerable comorbidities who presented with exertional dyspnea and was diagnosed with synchronous adenocarcinomas of the lung and rectosigmoid colon. Comprehensive diagnostic evaluation—including imaging, histopathology, immunohistochemistry, and next-generation sequencing—confirmed the independent origin of both tumors, revealing a shared KRAS (p.G12V) mutation along with distinct additional genomic alterations in each lesion. This case underscores the critical role of integrated molecular and pathological assessment in accurately distinguishing synchronous primary malignancies from metastatic lesions. This report highlights the need for a multidisciplinary strategy in the diagnosis and management of synchronous MPMTs, particularly in elderly individuals with complex disease biology.
Keywords: colorectal cancer; KRAS mutation; lung adenocarcinoma; multiple primary tumors; synchronous malignancy